Dampak Pelaksanaan Merdeka Belajar: Kampus Merdeka Di Universitas Trilogi - Aty Herawati; Kabul Wahyu Utomo; Rudi Setiawan; Rizki Dito Subekti (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Education is a step of liberation through knowledge. The Ministry of Education and Culture seeks to promote the liberalization of the education system through various efforts through Permendikbud No. 3 of 2020 concerning National Standards for Higher Education. Universities must be able to provide changes to students and have readiness before completing education. This study discusses the impact that results from the implementation of the Merdeka Learning Campus Merdeka. Using a qualitative research method with a descriptive approach with data collection through the distribution of survey forms to the entire academic community of Trilogy University. The results show that the majority of the academic community, both Lecturers, Students, and Education Personnel, are aware of the MBKM program. This program is expected to provide benefits to the economic and social aspects, one of which is entrepreneurship. This is because the Trilogy University campus places great emphasis on all students having an entrepreneurial spirit. This principle is in accordance with the vision and mission of the university.Keywords: MBKM; Qualitative; Entrepreneurship Abstrak:Pendidikan adalah langkah pembebasan melalui ilmu pengetahuan. Kementerian Pendidikan dan Kebudayaan berupaya menggalakkan pembesasan sistem pendidikan dengan berbagai upaya melalui Permendikbud Nomor 3 Tahun 2020 tentang Standar Nasional Pendidikan Tinggi. Universitas harus mampu memberikan perubahan kepada peserta didik dan mempunyai kesiapan sebelum menyelesaikan pendidikan. Penelitian ini membahas tentang dampak yang hasilkan dari pelaksanaan Merdeka Belajar Kampus Merdeka. Menggunakan metode penelitian kualitatif dengan pendekatan deskriptif dengan pengumpulan data melalui penyebaran borang survei kepada seluruh sivitas akademika Universitas Trilogi. Hasil menunjukkan mayoritas sivitas akademika, baik Dosen, Mahasiswa maupun Tenaga Kependidikan mengetahui program MBKM. Dengan adanya program ini diharapkan dapat memberikan manfaat kepada aspek ekonomi dan sosial salah satunya adalah kewirausahaan. Hal ini karena kampus Universitas Trilogi sangat menekankan kepada seluruh mahasiswa untuk berjiwa wirausaha. Prinsip ini sesuai dengan visi dan misi yang dimiliki universitas.Keywords: MBKM; Kualitatif; Kewirausahaan